Validation of a multiplexing technique to determine the intrathecal, polyspecific antiviral immune response in multiple sclerosis. (1st December 2016) - Huss, André; Buttmann, Mathias; Brecht, Isabel; Weishaupt, Andreas; Otto, Markus; Tumani, Hayrettin
ABSTRACT: Background: Beside the determination of oligoclonal bands (OCBs) as a diagnostic biomarker in multiple sclerosis (MS), the presence of an intrathecal production of antibodies against the neurotropic viruses measles (M), rubella (R) and Varicella-Zoster (Z), the so called MRZ reaction (MRZR) is an even more specific diagnostic biomarker in MS. Methods: We compared and validated the determination of the MRZR in 97 cerebrospinal fluid (CSF) and serum sample pairs of a bead-based multiplexing technique and a classical enzyme-linked immunosorbent assay (ELISA). Results: Conformity of 94% (M), 94% (R), 94% (Z), 96% (H) and 97% for the interpretation of the MRZR was obtained. Conclusion: Based on our findings of high conformity between the multiplex technique and classical ELISA, as well as the time and cost savings multiplexing allows, we conclude that the multiplexing technique is applicable as a diagnostic tool for the determination of the MRZR.